2015
DOI: 10.1002/cplu.201500015
|View full text |Cite
|
Sign up to set email alerts
|

Assemblies of Copper Ferrite and Palladium Nanoparticles on Silica Microparticles as a Magnetically Recoverable Catalyst for Sonogashira Reaction under Mild Conditions

Abstract: Copper ferrite and palladium nanoparticles assembled on silica microparticles are prepared successfully and characterized by scanning electron microscopy, transmission electron microscopy, electron‐dispersive X‐ray analysis, X‐ray diffraction, thermogravimetric analysis, atomic absorption spectroscopy, and infrared studies. The catalyst is applied effectively for the Sonogashira coupling reaction of aryl iodides and bromides under heterogeneous and phosphine‐free reaction conditions. The reactions proceed at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…Further, the XRD pattern was compared with JCPDS standard (no. 05–0681) and confirmed the formation of Pd‐NPs with cubic (face‐centred cubic) crystal structure, which is also consistent with earlier reports …”
Section: Resultssupporting
confidence: 92%
“…Further, the XRD pattern was compared with JCPDS standard (no. 05–0681) and confirmed the formation of Pd‐NPs with cubic (face‐centred cubic) crystal structure, which is also consistent with earlier reports …”
Section: Resultssupporting
confidence: 92%
“…Kohler and co‐workers reported that the Pd/C‐catalysed Sonogashira reaction of iodobenzene with phenylacetylene without the addition of CuI or PPh 3 gives TOF = 1184 h −1 and TON =592 . Gholinejad and Ahmadi reported that the Sonogashira reaction over Pd–CuFe 2 O 4 /SiO 2 catalyst gives TOF = 10.97 h −1 . Under similar conditions, Basu and co‐workers, Metin and co‐workers and Gao and co‐workers reported the Sonogashira reaction with Pd/Cu‐ARF(II) (TOF = 43.43 h −1 ), Cu 48 Pd 52 /RGO (TOF = 145.26 h −1 ) and MMT/Pd‐Cu (TOF = 6.06 h −1 ) catalysts, respectively.…”
Section: Resultsmentioning
confidence: 85%
“…This spinel was linked to a silica surface through an aminopropylsilaneoxy linker, and over this material PdNPs were deposited to obtain material 66. The catalyzed Sonogashira reaction was carried out using different functionalized iodo-and bromoarenes [112], the presence of electron-withdrawing groups at the p-position of the haloarene enhancing the chemical yield. It should be pointed out that the magnetic decantation of the catalyst and its reuse had a negative impact on the final yield, as it was explained by the high palladium leaching (6%), according to AAS analysis of the crude solution.…”
Section: Magnetic Material-supported Palladium Catalystsmentioning
confidence: 99%